A novel HLA allele, HLA‐C*15:02:01:04, identified in a Taiwanese individual. (12th March 2017) - Yang, K. L.; Ng, J.; Lazaro, A.; Lin, P. Y.
Abstract : One nucleotide substitution at residue 1924 of HLA‐C*15:02:01:01 results in a novel allele, HLA‐C*15:02:01:04 .